THE CONCEPT OF HUMANKIND ACCORDING TO CHRISTIAN PHILOSOPHY (IMAGO DEI) AND ITS IMPLICATIONS FOR CHRISTIAN RELIGIOUS EDUCATION WITHIN THE CHURCH, FAMILY, AND EDUCATIONAL INSTITUTIONS - Hamonangan Masasko Anthoni; Suranto; Agustria Empi; Ellya Nora Manurung (CV Naskah Aceh, 2026)
The concept of humankind from a Christian philosophical perspective is rooted in the teaching of Imago Dei, the belief that humans are created in the image and likeness of God. This understanding affirms human dignity as beings possessing intrinsic values, rationality, freedom, moral responsibility, and a purpose in life. This study aims to analyze the philosophical and theological meaning of Imago Dei and its implications for the development of Christian Religious Education (CRE). In the context of CRE, the concept of Imago Dei has significant implications for educational goals, learning methods, the relationship between teachers and students, and the formation of Christian character. The research method used is a literature review with a descriptive-analytical approach to the concept of humankind according to Christian philosophy and its relevance in contemporary Christian religious education. The results indicate that Imago Dei not only affirms human identity as God's creation but also serves as the basis for education oriented toward character formation, the development of spiritual potential, and the affirmation of one's calling in the light of Christ. Christian Religious Education must therefore function as a means of transformation that guides students to live in accordance with their dignity as images of God.